Climate change complicates efforts to ensure survival and recovery of St. Lawrence Estuary beluga. (December 2021) - Williams, Rob; Lacy, Robert C.; Ashe, Erin; Hall, Ailsa; Plourde, Stéphane; McQuinn, Ian H.; Lesage, Véronique
Abstract: Decades after a ban on hunting, and despite focused management interventions, the endangered St. Lawrence Estuary (SLE) beluga ( Delphinapterus leucas ) population has failed to recover. We applied a population viability analysis to simulate the responses of the SLE beluga population across a wide range of variability and uncertainty under current and projected changes in environmental and climate-mediated conditions. Three proximate threats to recovery were explored: ocean noise; contaminants; and prey limitation. Even the most optimistic scenarios failed to achieve the reliable positive population growth needed to meet current recovery targets. Here we show that predicted effects of climate change may be a more significant driver of SLE beluga population dynamics than the proximate threats we considered. Aggressive mitigation of all three proximate threats will be needed to build the population's resilience and allow the population to persist long enough for global actions to mitigate climate change to take effect. Highlights: Decades after a hunting ban, the St. Lawrence Estuary beluga failed to recover. Improved calf survival is vital to sustained population growth. We explored threats to recovery: ocean noise; contaminants; and prey limitation. Climate change is most significant driver of SLE beluga population dynamics. Mitigation of all three proximate threats needed to build climate resilience.